Corneal Perforation Caused by Eyelid Margin Trichilemmal Carcinoma: A Case Report and Review of Literature - Zhang, Liying; Lin, Zhirong; Wu, Huping; Ou, Shangkun (Frontiers in Medicine, 2022)
Background: Trichilemmal carcinoma (TLC) is a rare malignant adnexal tumor most commonly found in the elderly, usually affecting the scalp, eyelids, neck and face. Here, we first reported a rare case of corneal perforation caused by eyelid margin TLC. Case presentation: A 68-year-old female presented with two months history of unprovoked redness, pain and blurred vision in the left eye. On slit-lamp examination, a 1×2mm sized aseptic corneal perforation embedded by iris prolapsed was noted. Upon detailed case investigation, we speculated that the severe meibomian gland dysfunction (MGD) and subsequent Blepharokeratoconjunctivitis (BKC) could have led to corneal perforation. The patient underwent penetrating keratoplasty to prevent ulcer enlargement and infection. However, several tiny nodules gradually developed on the eyelid margin postoperatively, accompaniedby with bleeding, burst and madarosis postoperatiely. Subsequently, biopsy revealed the growth of TLC on the eyelid margin, and lesionectomy was immediately conducted During the 1-year follow-up period, no local recurrence or metastasis was observed. Conclusions: To date, there has not been any report of corneal perforation caused by eyelid margin TLC. Consideration of the clinical presentation, feature and histopathologist will be benefit for the dignoses and treatment of TLC. Ensuring a smooth eyelid margin by total excision of TLC and consistent followup of patient will avoid recurrence.